Exploring the Relationship between Preservice Science Teachers’ Beliefs and Self-Regulated Strategies of Studying Physics: A Structural Equation Model - Tanti; Maison; MUKMININ, Amirul; Syahria; HABIBI, Akhmad; Syamsurizal (Journal of Turkish Science Education, 2018)
This study aimed at exploring a structural equation model on the relationship between preservice science teachers’ beliefs and self-regulation strategies of studying physics. The sample of the study consisted of 248 pre-service science teachers drawn from department of physics education at one state university and one state Islamic university in Jambi, Indonesia. The Colorado learning attitudes about Science Survey (CLASS) was used to measure their beliefs of physics and physics learning. Furthermore, motivated strategies for learning questionnaire (MSLQ) was also deployed to measure their self-regulation strategies on studying physics. Variance-based structural equation modeling (SEM with PLS) showed that sophisticated beliefs were positively correlated to the use of elaboration, organization, and metacognitive strategies whilst naïve beliefs were positively correlated with the use of rehearsal and elaboration methods. This study provides insightful implications for educators, especially lecturers, on how to plan, design, and practice the appropriate and effective pedagogical strategies to replace naïve beliefs with sophisticated ones, and to enhance the use of self-regulated strategies in studying physics.